(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study examines the linguistic hegemony of English in Indian higher education and its continuing influence as a legacy of colonial rule. It explores how the privileged status of English reinforces social inequalities linked to caste, class, and geographical location, thereby shaping students’ academic performance, participation, and sense of self-worth. The paper highlights the challenges faced by students from non-English-speaking backgrounds, particularly in academic communication, evaluation, and knowledge production, where unequal power relations often marginalize alternative linguistic expressions. Drawing on empirical evidence and existing scholarship, the study critically analyzes the role of English language instruction and institutional accountability in addressing these disparities. It further raises concerns about access, inclusion, and equity within higher education spaces dominated by English. The study ultimately emphasizes the need for a more inclusive multilingual approach that integrates regional languages alongside English to promote educational justice, enhance learner confidence, and support diverse intellectual traditions in Indian higher education.